TRENDS IN PUBLIC-PRIVATE PARTNERSHIPS AT THE PRESENT STAGE - Oksana Pankratova (Вестник Северо-Кавказского федерального университета)
The article is devoted to topical issue ofpublic-private partnerships as a tool for attracting investments into the regional economy. Studied the specificity of realization of socially significant projects by non-state investors. Discusses the formation and development of mechanisms of public-private partnerships, analyzed dificulties and effective approaches to its construction.